(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This scientific article reveals the nature of cultural relations between socialist countries using the example of the Uzbek SSR and the German Democratic Republic. Only the example of the GDR shows the general features of cultural relations in the Uzbek SSR during the Soviet period.